Disparities in prostate cancer epidemiology: a comparative analysis of West Africa and Europe - Warner, Aleece; Chinegwundoh , Francis (Journal of Global Medicine, 2025)
Prostate cancer remains a leading cause of morbidity and mortality worldwide, disproportionately affecting black men. This review examines the differences in prostate cancer incidence and mortality rates between West Africa and Europe. While prostate cancer is more prevalent in Europe, primarily attributed to widespread screening programmes, West Africa faces significant challenges, including underdeveloped cancer registration systems, low public awareness, and limited access to screening. These factors lead to underreporting of incidence rates, yet higher mortality rates. In addition, this narrative review explores the role of environmental and lifestyle factors, including high levels of chronic stress and exposure to pollutants, as additional risk factors for prostate cancer in West Africa compared to European countries. As the global incidence of prostate cancer is projected to increase, implementing region-specific interventions and targeting modifiable lifestyle factors will be vital in alleviating the burden in West Africa. Addressing these disparities is essential for improving early detection, enhancing survival outcomes, and promoting more equitable prostate cancer care.